Analysis of a Higher-Order Thinking Skills Assessment Instrument Leveraging Wordwall Embedded in Google Sites for Newton’s Laws Instruction - Sari, Lindya; Sabani, Sabani; Solikin, Solikin; Simangunsong, Rufasa Mutia Salwa; Situmorang, Agtrimas; Aldina, Dayang; Nadiyah, Nadiyah (Lensa: Jurnal Kependidikan Fisika, 2025)
This study aimed to develop and validate a Higher-Order Thinking Skills (HOTS) assessment instrument that leverages Wordwall activities embedded in Google Sites for teaching Newton’s Laws. A quantitative-descriptive design with an evaluative approach was employed. Nineteen Grade XI science students from Gajah Mada Private Senior High School were selected through purposive sampling. Item analysis examined validity, reliability, difficulty level, and discrimination power. Of the ten multiple-choice items constructed, five (50 %) met validity criteria, and the instrument achieved a reliability coefficient of 0.492, indicating adequate internal consistency. Difficulty indices classified three items as difficult and seven as moderate, while discrimination indices categorized two items as very good, three as good, one as fair, and four as poor. Students’ mean achievement score of 37.89 % suggests limited familiarity with HOTS-oriented questions. Pedagogically, embedding Wordwall in Google Sites enhanced learner engagement, reduced test anxiety, increased comfort, and simplified teachers’ post-test analysis through automated scoring. Consequently, the HOTS-based instrument is not only statistically sound but also practically effective for supporting digital physics instruction.